2019
DOI: 10.33395/sinkron.v3i2.10069
|View full text |Cite
|
Sign up to set email alerts
|

Multi-criteria for Selection of SmartPhone Brands Product using AHP-TOPSIS Method

Abstract: Today's communication is very important to do, this can be done by using communication tools that are currently being used by everyone, none other than SmartPhone, so people are competing to get it. Many found difficulties in choosing a SmartPhone Brand Product that suits the wishes of each user from a number of alternatives such as Advance, Xiaomi, OPPO, SAMSUNG, and VIVO, because many criteria must be considered such as memory capacity, battery durability, sharpness of capture camera, the form of design prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 6 publications
0
6
0
1
Order By: Relevance
“…Several previous studies have succeeded in combining the AHP and TOPSIS methods in decision making (Al Azis et al, 2017;Du & Gao, 2020;Santika & Handika, 2019). Combining the AHP and TOPSIS methods can produce more objective rankings quickly and precisely, by combining the AHP and TOPSIS methods, it can produce better recommendations (Akmaludin & Badrul, 2019;Berdie et al, 2017;Y. W. Du & Gao, 2020;Hanine et al, 2016;Jatiningrum et al, 2022;Santika & Handika, 2019).…”
Section: Preliminarymentioning
confidence: 99%
“…Several previous studies have succeeded in combining the AHP and TOPSIS methods in decision making (Al Azis et al, 2017;Du & Gao, 2020;Santika & Handika, 2019). Combining the AHP and TOPSIS methods can produce more objective rankings quickly and precisely, by combining the AHP and TOPSIS methods, it can produce better recommendations (Akmaludin & Badrul, 2019;Berdie et al, 2017;Y. W. Du & Gao, 2020;Hanine et al, 2016;Jatiningrum et al, 2022;Santika & Handika, 2019).…”
Section: Preliminarymentioning
confidence: 99%
“…(Paramita et al, 2017). Metode AHP membantu dalam menentukan prioritas dari beberapa kriteria (Akmaludin & Badrul, 2019)dengan melakukan analisa perbandingan berpasangan (Pairwise Comparison) dari masing-masing kriteria. Proses matematis pada AHP secara umum adalah menentukan preferensi pada setiap tingkat hierarki.…”
Section: Pendahuluanunclassified
“…To improve decision support, the AHP method is frequently integrated with other approaches. Combining the AHP method has been used in several studies, including choosing smartphone purchases using the AHP-VIKOR combination [15], assisting in loan decisions using the AHP and TOPSIS combination [16], choosing wind farm installation locations using the AHP and TOPSIS in Eastern Macedonia and the Thrace region of Greece [17], and combining the AHP and MILP methods. for making strategic decisions in designing global supply chain networks [18], for selecting digital technology using a combination of fuzzy logic and AHP [19], for determining cooperative lending using a combination of AHP, BORDA, and TOPSIS methods [20], and many other topics.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that using AHP in conjunction with the SMART technique improves decision support. These two approaches have been blended in several prior studies, including those that dealt with grading systems [21], employee performance rewards and penalties [22], employee promotions [23], supplier selection [24][25], and many more. This reseacrh attempts to combine AHP and SMART in this situation to create a decision support system for hiring the best candidates.…”
Section: Introductionmentioning
confidence: 99%